ニシ オングル トウ ノ チズ サクセイ ニツイテ - 吉田, 新生; ヨシダ, アラオ; 斎藤, 佳夫; サイトウ, ヨシオ; YOSHIDA, Arao; SAITO, Yoshio (国立極地研究所, 1965)
P(論文) 0ne sheet map of West Ongul Island, separated by a narrow strait from East Ongul Island in which Syowa Station is situated, was compiled with 1 : 5,000 scale. The plotting, based on 4 ground control points and 2 models of vertical air photographs taken by the 6 th Japanese Antarctic Research Expedition, was carried out by using a Wild Stereo Plotter. departmental bulletin paper